Oliveira Vianna e o projeto do Estado nacionalista, corporativo e autoritário - Rett, Lucas Paes (2026)
This dissertation examines the State project proposed by Oliveira Vianna during the Vargas administration. Objective: To analyze the key issues that synthesize: (1) Vianna’s belief in the construction of nationalism as a means of unifying and modernizam the country; (2) the understanding of Vianna's intellectual overlap with the bureaucratic structuring of the authoritarian State; and (3) the relevance of corporatism in Vianna's intellectual trajectory and its subsequent role in the construction of this state model. Justification: This research is relevant as it places Oliveira Vianna as a central figure in the national-state building project that became hegemonic after 1930, with Getúlio Vargas’s rise to power. Theoretical-Methodological Aspects: The methodology consists of the study of Oliveira Vianna’s primary works through the lens of Intellectual History and its specific analytical frameworks. Furthermore, it considers the technical roles held by Vianna during the Estado Novo. Throughout this process, we demonstrate how the three pillars—nationalism, authoritarianism, and corporatism—unify within Vianna’s project. Results: It was observed that while the ideologue influenced the theoretical framework that resulted in the Constitution of 1937, his most effective form of intervention occurred through strictly technical functions. Vianna contributed to both the theory and practice of an authoritarian political culture in Brazil and to the establishment of a Labor Justice system rooted in corporatist values